2012
DOI: 10.2355/isijinternational.52.2013
|View full text |Cite
|
Sign up to set email alerts
|

Change in Inclusion Composition during CaO Flux Powder Blowing under Reduced Pressure

Abstract: To examine the reaction mechanism of the variation of calcium content in inclusions and the molten steel and the effect of flux composition on the reaction, the variations of molten steel content and inclusion content during CaO, 60%CaO-40%CaF2 or 50%CaO-50%CaSi powder blowing onto the molten steel under reduced pressure were investigated with 15 kg scale experiments. From the experimental results, it was found that the inclusion composition was changed from Al2O3 to Al2O3-CaO by CaO flux that did not contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…5, where the spots with the shape of box and solid triange are reported by M. Numata et al 3,4) and G. W. Yang et al 1,2) respectively and their results is almost in accordance with the ones in present work in the case of T.Ca/T.O less than 1. steel less than 0.5, Al 2 O 3 content in inclusion is very high even close 90%, which indicates the type of inclusion is Al 2 O 3 inclusion or low modified calcium aluminates; In the case of T.Ca/T.O in steel greater than 0.5 and less than 1.5, the type of inclusion is Al 2 O 3 -CaS inclusion.…”
Section: Effect Of Tca/to On Al 2 O 3 Content Of Inclusionssupporting
confidence: 91%
See 1 more Smart Citation
“…5, where the spots with the shape of box and solid triange are reported by M. Numata et al 3,4) and G. W. Yang et al 1,2) respectively and their results is almost in accordance with the ones in present work in the case of T.Ca/T.O less than 1. steel less than 0.5, Al 2 O 3 content in inclusion is very high even close 90%, which indicates the type of inclusion is Al 2 O 3 inclusion or low modified calcium aluminates; In the case of T.Ca/T.O in steel greater than 0.5 and less than 1.5, the type of inclusion is Al 2 O 3 -CaS inclusion.…”
Section: Effect Of Tca/to On Al 2 O 3 Content Of Inclusionssupporting
confidence: 91%
“…Yang et al 1,2) studied the effect of calcium addition on the variation of inclusion composition in low carbon Al-killed steel with induction vacuum furnace and found that the Al 2 O 3 content in inclusions linearly decreased by increasing T.Ca/T.O in steel and it disappeared when T.Ca/T.O exceeded 3 and CaS/CaO of the inclusions linearly increased by increasing S/T.O in steel. Numata et al 3,4) investigated the calcium consumption and calcium addition pattern on the change of inclusion composition. They found CaO-CaS typed inclusions in steel with 0.0015% sulfur content after calcium (Received on March 1, 2016; accepted on April 7, 2016) Inclusions in slab samples with various total calcium, oxygen and sulfur content were investigated in low carbon aluminum killed steel (LCAK steel) with low sulfur content based on industrial experiments and the relationship between steel and inclusions was studied by analyzing inclusions characteristic being detected by SEM-EDS.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the T.Ca/T.O ratio should be controlled above 0.91 in order to get a good calcium treatment result. 30,31 T.Ca/T.O was less than 0.5 in the current study, which lead to the oxide inclusions located outside of the 1873 K low-melting region after P-ESR process.…”
Section: Thermodynamics Of Oxide Inclusions and Calcium Sulphide Evol...mentioning
confidence: 53%
“…Therefore, it is very important to study the phase composition of inclusions during calcium treatment. [24] Numata et al [25] studied the effect of calcium content on the modification of inclusions by laboratory experiments. Verma et al [26] demonstrated that the inclusion size decreased significantly after Ca treatment, mainly from 10-20 µm to 1-2.5 µm.…”
Section: Introductionmentioning
confidence: 99%